Strategi Manajemen Talenta untuk Menghadapi Tantangan Era Revolusi Industri 4.0 - Shafira Putri R; Resti Monika H.G; Delilah Azmi W.P (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Industrial Revolution 4.0 has brought significant changes to the world of work, requiring organizations and individuals to adapt quickly to new technologies and evolving skill demands. This study aims to explore effective talent management strategies to address the challenges and capitalize on the opportunities in this era of disruption. Through an in-depth literature review of relevant sources, this study identifies current trends in human resource management and related technologies.The findings indicate that enhancing both hard and soft skills is crucial. Hard skills, such as proficiency in digital technologies and data analysis, are essential to navigate technological advancements. Soft skills, including communication, collaboration, and leadership, are vital for adapting to the new work dynamics. Furthermore, foreign language proficiency is increasingly important for collaboration and competition in the global market. Additionally, practical training, both within and outside the work environment, is necessary to apply knowledge and develop relevant skills. Implementing these strategies will provide a strong foundation for organizations to maintain competitiveness and maximize employee potential in the dynamic digital age. Organizations are encouraged to adopt a proactive approach in developing their talent to ensure long-term success.